'Just because I'm old it doesn't mean I have to be fat': a qualitative study exploring older adults' views and experiences of weight management. Issue 2 (5th February 2019) - Jackson, Sarah E; Holter, Linn; Beeken, Rebecca J
Abstract : Objectives: The aim of this study was to explore older adults' beliefs about the appropriateness of weight management, and how their experiences and expectations of weight management have changed as they have got older. Design: Qualitative semistructured interview study. Setting: UK. Participants: Older adults (≥65 years) in the UK who had recent (<5 years) experience of trying to manage their weight (n=15; 12 women; 73% white British). Results: Data were analysed using thematic analysis. Emergent themes highlighted that weight remained a concern for many older adults, although having a high body weight was seen to be more acceptable at older than younger ages. Excess weight was reported to have negative consequences for health and well-being which participants felt could be alleviated by losing weight. Participants were motivated to lose weight for appearance and health reasons, but mentioned finding it harder to lose weight as they had got older and generally felt they had received limited guidance on weight management from health professionals. Conclusions: The views of our participants highlight the need for further research into safe and effective methods of weight loss for older people and indicate that advice and support from health professionals would be welcomed.